Republic of Tajikistan : First Assessment Under the 2008 Staff-Monitored Program. (IMF Staff Country Reports; Country Report, 2008)
This paper on the First Assessment Under the 2008 Staff-Monitored Program (SMP) for the Republic of Tajikistan discusses the ongoing global financial crisis. The main purpose of the SMP is to allow the authorities to reestablish their credibility after a serious episode of misreporting to the IMF. Revenue collection was stronger than projected, mostly reflecting high nominal growth and imports. Monetary and exchange rate policies will have to focus on maintaining external stability. Moreover, a possible sharp depreciation of main trading partners' currencies may require further exchange rate adjustment.